Perron-Frobenius, principal eigenvalue, Maximum Principle: a personal itinerary - Italo Capuzzo Dolcetta (Rendiconti di Matematica e delle Sue Applicazioni, 2020)
This paper dedicated to Umberto Mosco revisits a line of my research starting in the early 70's in the aim of identifying a path connecting different concepts which play a role in elliptic pde's, spectral theory and optimal control.